DINAMIKA BERPAKAIAN PELAJAR SEKOLAH DASAR (SD) DI KABUPATEN SOLOK MASA PEMERINTAHAN GAMAWAN FAUZI 1995-2005 - Uci Permata Sari; Melia Afdayeni; Suriani Suriani; Kori Lilie Muslim (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This paper aims to look at the changes in the dress of school students in Solok Regency during the reign of Gumawan Fauzi. This change was motivated by the issuance of regional regulation letter No. 6 of 2002 concerning Muslim and Muslim women's clothing. This title was taken from 1995 to 2005. The type of research used is qualitative research. The method used in this research is historical research method using steps (1) heuristics or source collection (2) source criticism, (3) interpretation, (4) historiography. From the results of the research conducted, during the reign of Mr. Gamawan Fauzi found that there was a change in the form of dress for elementary school students in Solok Regency, this was caused by a circular issued by Mr. Gamawan Fauzi regarding the way elementary school (SD) students dressed. From 1995 to March 2002 the clothes worn by elementary school students were wearing short-sleeved shirts for both men and women and wearing short skirts for women while men for men also wore short pants and did not wear headscarves for women, whereas after being expelled regional regulation letter No. 6 of 2002, namely that there was a change in the dress of female and male students wearing long sleeves and long male skirts for female students and wearing headscarves while male students wore trousers. While the meaning of changing the clothes of school students is: This change of clothes also has a meaning which means to protect the private parts, especially for female students, to guard against disturbances that will damage the genitals and also by wearing closed clothes also avoid the fires of hell in the future and also fortify themselves and the next generation of the nation so that they do not fall into a culture that is not in accordance with the teachings of Islam